Om Malkekvæget i Danmark. Foredrag ved den 15de danske Landmandsforsamling 1883. - Buus, N. P. J. (Tidsskrift for Landøkonomi, 2018)
Om Malkekvæget i Danmark. Foredrag ved den 15de danske Landmandsforsamling 1883.